PENGEMBANGAN STRATEGI PEMASARAN KAWASAN EKOWISATA DI INDONESIA YANG BERBASIS PADA PENINGKATAN EKONOMI LOKAL - Vendy Wijaya (Universitas Katolik Widya Karya Malang, 2019)
This study aims to determine the potential of ecotourismlocated in Indonesia, analyze the elements of ecotourismmanagement and public participation to the economic andenvironmental aspects as well as formulating marketingstrategies. The results showed that in the management of thetourism element of ecotourism there are still somedeficiencies. Local communities haven’t been intensivelyinvolved and yet derive optimal benefits from ecotourism. Dueto ecotourism hasn’t contributed much to stimulate theeconomy of local communities. In order to meet the criteria ofthe concept of ecotourism, the main efforts of local communityinvolvement is needed. Viewed from the aspect ofconservation, has been their natural and cultural preservationprogram, and of the economic aspects that benefit localcommunities.